ANALISIS LAPORAN REALISASI ANGGARAN PENDAPATAN DAN BELANJA DESA PADA DESA AMAN DAMAI KEC. SIRAPIT KABUPATEN LANGKAT TAHUN 2018-2020 - Dea Novita Sari (EKSPOLHUM, 2024)
This study aims to find out the report on the realization of the village income and expenditure budget in 2018-2020 in Aman Damai Village, Sirapit District, Langkat Regency. This study uses a descriptive method with a qualitative approach with interviews with related village officials. The results of the study indicate that the sources of income for Aman Damai Village are village original income and transfer income and expenditures issued by Aman Damai Village, namely the field of development implementation, the field of village administration, the field of community development and the field of community empowerment. The analysis of the realization of the village income and expenditure budget reports has been realized well, although some of the budgets have not been realized in their entirety.